Digital Image Analysis-Based Evaluation of Claudin-1 and Claudin-7 Delocalization in Cutaneous Squamous Cell Carcinoma and in Its Precancerous State. (6th April 2022) - Xu, Lina; Pan, Yunlei; Tang, Shunli; Bai, Juan; Wu, Yinhua; Qiao, Jianjun; Fang, Hong
Abstract : Accumulating evidence has revealed that delocalization of the transmembrane proteins, Claudin-1 and Claudin-7, to the cytoplasm and/or nucleus occurs in various tumors. However, their subcellular distribution in terms of the membrane, cytoplasm, and nucleus and relationship with signaling pathways have not been elucidated during carcinogenesis. We first determined the expression of these proteins in the membrane, cytoplasm, and nucleus using ImageJ software and automatically collected the immunohistochemical quantification of dysplasia (actinic keratosis (AK)), carcinoma in situ (CIS; Bowen's disease (BD)), and invasive cutaneous squamous cell carcinoma (SCC) for digital image analysis (DIA). The activity of p-ERK, p-AKT, and p-mTOR and their correlation with subcellular Claudin-1 and Claudin-7 were also performed. Finally, we validated Claudin-1 and Claudin-7 delocalization at the cytoplasm and nucleus in cultured human normal keratinocytes and cutaneous SCC cells. Claudin-1 and Claudin-7 were delocalized as revealed by membranous, cytoplasmic, and nuclear staining in sun-exposed skin, AK, BD, and SCC. In BD, both membranous and cytoplasmic Claudin-1 (nuclear Claudin-1 decrease but no significant difference) were higher than AK, while Claudin-7 almost had the opposite situation. In SCC, cytoplasmic and nuclear Claudin-1 (membranous Claudin-1 no significant difference) was lower than in AK and sun-exposed skin, while Claudin-7 had higher membranous and cytoplasmic but lower nuclear expression. Moreover, p-AKT and p-mTOR (but not p-ERK) were downregulated in the SCC. Subcellular Claudin-1 and Claudin-7 were not only correlated with each other, but also correlated with p-ERK in BD and p-AKT and p-mTOR in SCC. Together, these results imply the delocalization of Claudin-1 and Claudin-7 and their correlation with MAPK/ERK and PI3K-AKT-mTOR signaling pathways in tumorigenesis and infiltration in cutaneous SCC.